IslamicLegitimate purposes - Ahmad Vnos Hamadi (Journal of Madenat Alelem University College, 2015)
Legitimate objectives are, inter alia, wanted the street from the interests of the consequences of legal provisions dealt with the legitimate purposes of applications in the interpretation of the verse cited by the General purposes observed in all or most of the doors of the law and areas so that did not concern her remarks in a special type of Sharia major objectives and applications that addressed Search general purposes in bringing the interests and trials and follow what was revealed to him, and kindness to parents and reform among the people and applications that addressed research also general purposes in warding off evil, and is forbidden to follow the steps of Satan, and forbidding the ridicule of religion, and in special purposes, and charity to orphans, It is self-reform, and thinking about the revelations of Allah, and Allah Crown success